HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU YANG BEKERJA - Ranti Nopria; Juniar Ernawaty; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Exclusive breastfeeding is a nutrient that is highly needed by the baby in the first six months of life. Working mothers require family support to be able to carry out exclusive breastfeeding practices and work. This study aimed to determine the relationship of family support and exclusive breastfeeding.The research design used was a correlational study with cross sectional approach. The place of research was in the working area of Harapan Raya Health Center that the technique of selecting the posyandu area for the sample of this research was using cluster sampling, while purposive sampling technique was applied to determine the sample consisting of 154 respondents. The instruments used were questionnaries. The bivariate data analysis used was Chi Square. The results showed that 51,3% of respondents received high family support with 49,4% giving exclusive breastfeeding to their babies. The results of data analysis using the Chi Square test showed that there was a relationship between family support and exclusive breastfeeding for working mothers (p value = 0.000 < α 0.05). The results of this study are expected to be used as recommendation for the Health Center to provide information about the importance of exclusive breastfeeding for infants aged 0-6 months and the significance of family support for working and breastfeeding mothers to be able to give breast milk exclusively.Keywords: Breastfeeding, family support, working mother